STRUCTURE STUDY OF SOME LANTHANIDE'S OXIDES BY X-RAY DIFFRACTION AND PAIR POTENTIAL MODELING - Rammo, Nabil (Iraqi Journal of Science, 2024)
A number of Lnx Oy rare-earth oxides where Ln = La, Ce, Pr, Nd, Sm, Eu, Tb,Dy and Er, x=1, 2, 4, 6 and y=2, 3, 7, 11 have been studied by powderdiffractometry and pycnometry coupled with the simulation of their latticedimensions by empirically derived pair potentials using the GULP code.Crystallographic analysis showed the oxides exist in the tri, tetra and mixed tri-tetravalency with Bravias lattices: hexagonal- P, cubic- I and cubic- F as a result of theoxidation state assumed by the Ln element that may be caused by the nature of theoxide or preparation process involved. Unit cell volumes of the oxides that exhibitidentical Bravias lattices reflect a behavior that can be correlated with the atomicnumber of the Ln element whereby it decreases linearly by uncertainty notexceeding ca. 3%. The average bond lengths of Ln - O polyhedra in the sesquioxides(Ln2 O3) space group Ia3 also follow suit. The behavior is interpreted on aphenomenon known as lanthanide contraction.